The Principal’s Leadership In Managing Student Diversity: A Case Study Of The Implementation Of The Merdeka Curriculum - Hania, Nur; Khaudli, Muh. Imam (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2024)
This study aims to describe and analyze the role of the principal in managing student diversity during the implementation of the Merdeka Curriculum at MA Wanagading. Student diversity including social, cultural, academic, and learning needs demands school leadership that is inclusive and adaptable to change. While the Merdeka Curriculum has been widely studied, there is still a lack of research focusing specifically on leadership dynamics within Islamic schools, particularly in managing diverse student populations. This study employs a qualitative approach using a case study method. Data were collected through in-depth interviews with the principal, teachers, and students, as well as through observation of learning activities and documentation of school policies. The data were analyzed descriptively through the processes of reduction, presentation, and conclusion drawing. The findings show that the principal acts as an instructional leader, an innovation facilitator, and a promoter of an inclusive culture within the school. Several strategies were implemented, including teacher training on differentiated instruction, the development of adaptive learning policies, and strengthened communication with parents and the community to support student diversity. The study concludes that the successful implementation of the Merdeka Curriculum heavily relies on the quality of school leadership in managing student diversity. A transformative and collaborative principal role creates a more equitable, flexible, and student-centered learning ecosystem. This study offers a practical model for madrasah principals to balance curriculum flexibility with inclusivity, serving as a reference for diversity-based educational policy development.